(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The primary purpose of the prevention survey (TPS) is to monitor and enhance preventive health policies across various sectors in Flanders and Brussels, including schools, enterprises, local governments, childcare facilities, and healthcare institutions. This project is innovative in its comprehensive approach, utilising a triennial survey to gather data on a wide range of preventive health measures, not just focused on physical activity and sedentary behaviour, but also on nutrition, mental wellbeing, dental health, fall prevention, smoking, alcohol and drug use. Project or Policy Description. Development: TPS was developed by Flanders Institute of Healthy Living (NGO) in collaboration with key partners. This project is both research and practice-based, designed to evaluate and enhance preventive health policies across various settings. This was funded by the Flemish Department of Health. Implementation: The implementation involves distributing an online detailed questionnaire to various organisations to evaluate their preventive health policies on multiple themes. The data collection is carried out every three years to track progress and identify areas for improvement. Evaluation: The collected data are analysed to provide insights into the effectiveness of current health policies and practices. Within each health theme, the set of questions is based on several criteria for a qualitative preventive health policy. These quality criteria summarise the initiatives, measures, and facilities that constitute a qualitative preventive policy for the respective theme. The results are shared with: (1) participating organisations to help them enhance their preventive health strategies, and (2) partners in the preventive health sector and stakeholders to give them insights and inspiration for future interventions. Dissemination: The findings from TPS are disseminated through public reports and workshops. The results are also used to inform regional health policies and support the scaling up of successful interventions. Conclusions: TPS contributes significantly to the field of preventive health by providing valuable data that informs policymaking and practice. The project’s comprehensive approach and regular data collection offer critical insights for improving health promotion strategies and addressing health disparities across various sectors.